Recent Advances in Molecular-Imprinting-Based Solid-Phase Extraction of Antibiotics Residues Coupled With Chromatographic Analysis - Sun, Dani; Song, Zhihua; Zhang, Yue; Wang, Yixiao; Lv, Min; Liu, Huitao; Wang, Liyan; Lu, Wenhui; Li, Jinhua; Chen, Lingxin (Frontiers in Environmental Chemistry, 2021)
Abuse and residues of antibiotics cause great harm to organisms and the environment. Appropriate sample pretreatment is usually required for sensitive determination, because of the low contents presence of a variety of antibiotics in complicated matrices. Molecular-imprinting based solid-phase extraction (MISPE) has been widely used for sample pretreatment of antibiotics, using molecularly imprinted polymers (MIPs) as adsorbents. Herein, we comprehensively review the recent advances of MISPE of antibiotics, followed by chromatographic determination. Various SPE modes based on MIPs are briefly introduced, such as dispersive SPE, magnetic SPE, matrix solid-phase dispersion (MSPD). Then, several emerging preparation techniques for antibiotics MIPs are summarized including surface imprinting, nanoimprinting, living/controlled radical polymerization (LCRP), multi-template imprinting, multi-functional monomer imprinting and dummy template imprinting. Subsequently, applications of MISPE to analysis of a variety of antibiotics residues since 2018 are overviewed, including sulfonamides, quinolones, tetracycline and others. Finally, the preparation and application of antibiotics MIPs are prospected.